FORMULATION AND EVALUATION OF NIFEDIPINE SUSTAINED RELEASE TABLETS BY USING DIFFERENT POLYMERS - Pareek, Shraddha Pawan; Kumawat, Sunil; Sharma, Vijay; Sharma, Devender; Rathore, Devendra Singh (Journal of Biomedical and Pharmaceutical Research, 2019)
Oral drug delivery has been known for many years because the most generally utilized route of administration among all the routes that are explored for the general delivery of medication via various pharmaceutical products of different dosage forms. The reason that the oral route achieved such quality could also be partly attributed to its simple administration moreover because the ancient belief that by oral administration the drug is well absorbed because the food stuffs that area unit eaten daily. In fact the event of a pharmaceutical product for oral delivery, no matter its physical kind involves variable extents of optimization of dose kind characteristics at intervals the inherent constraints of GI physiology. The rationale for development of a extended release formulation of a drug is to enhance its therapeutic benefits, minimizing its side effects while improving the management of the diseased condition. The aim of the present investigation is to formulate and evaluate matrix tablets of Nifedipine using a mixture of polymers in view to sustain the drug release, reduce frequency of administration and improved patient compliance. In this research paper all evaluation parameter and stability studies also well discussed in well manner. Keyword: Matrix Tablets, Coating, Novel Drug Delivery System, Sustained Release Tablets